Synthesis and Biological Activity of 7-Benzyloxy and 7-Methoxy Flavone - Alam, Sayed; Jalil Miah, M. A.; Islam, Azizul (Biological Sciences - PJSIR, 2007)
. Benzyl and methyl d erivatives of 7-hydroxyflavone were synth esized from 2-hyd roxy-4 -benzyloxy acetophenon e and 2-hydroxy -4-methoxyacetophenone, respectivel y, via chal cone precu rsor and by the treatment with DMS0/ 12 , diphenyl sul ph ide and d ichloro d icyan o qu i n on e (DDQ). The an t i bacteri al and antifunga l activ i ty of these flavones and thei r correspond i ng chalcones were fou nd in vitro by the fi l ter paper d i sc diffu si on method and poi son ed food techn iq ue .